2004
DOI: 10.1182/blood-2003-09-3139
|View full text |Cite
|
Sign up to set email alerts
|

Hephaestin is a ferroxidase that maintains partial activity in sex-linked anemia mice

Abstract: Hephaestin (Hp) plays an important role in intestinal iron absorption and is predicted to be a ferroxidase based on significant sequence identity to the serum multicopper ferroxidase ceruloplasmin. Here, we demonstrate that Hp has both amine oxidase and ferroxidase activity in cultured cells and primary intestinal enterocytes with the use of both gel and solution assays. The specificity of the activity is shown by immunoblotting, immunoprecipitation, and immunodepletion experiments. Surprisingly, the truncated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(79 citation statements)
references
References 48 publications
3
73
0
3
Order By: Relevance
“…The sla mouse, however, represents a sex-linked anemia that maps to a Heph allele carrying an in-frame mutation leading to expression of a protein missing 194 internal residues (26). This protein does exhibit ferroxidase activity but does not traffic to the basolateral membrane of enterocytes in support of iron efflux from the gut into the circulation (53,54). sla mice are anemic as a result even though they hyperaccumulate iron in their intestinal epithelia.…”
Section: Genetic Arguments For Ferroxidases As a Key To Iron Homeostasismentioning
confidence: 99%
“…The sla mouse, however, represents a sex-linked anemia that maps to a Heph allele carrying an in-frame mutation leading to expression of a protein missing 194 internal residues (26). This protein does exhibit ferroxidase activity but does not traffic to the basolateral membrane of enterocytes in support of iron efflux from the gut into the circulation (53,54). sla mice are anemic as a result even though they hyperaccumulate iron in their intestinal epithelia.…”
Section: Genetic Arguments For Ferroxidases As a Key To Iron Homeostasismentioning
confidence: 99%
“…We have evidence that Fpn is also expressed in astrocytes and neurons (data not shown). As mentioned previously, sla mutant mice express a truncated, partially active form of Heph in non-CNS tissues (Vulpe et al, 1999;Chen et al, 2004). We therefore compared the expression of Heph and Fpn in the CNS of sla and wild-type mice by Western blot analysis.…”
Section: Hephaestin and Ferroportin Are Expressed In The Adult Mouse mentioning
confidence: 99%
“…Another copperdependent ferroxidase, hephaestin (Heph), was identified in duodenal enterocytes (Vulpe et al, 1999) and was also shown to play a role in iron efflux. In the sex-linked anemia (sla) mouse, a partial deletion of the heph gene results in the expression of a truncated Heph protein that exhibits only partial ferroxidase activity (Vulpe et al, 1999;Chen et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…76 Placental transfer of maternally injected radioiron in the second half of pregnancy was not different between sla and wild-type mice, although sla pups accumulated less radioiron given in the maternal diet throughout pregnancy. 76 It is worth pointing out that the sla allele of Heph retains partial ferroxidase activity, 77 so the minimally perturbed placental iron transfer in sla pups may underrepresent the degree to which Heph is important for placental iron transport. A third ferroxidase in the placenta has been described by Danzeisen et al, 78 who detected an intracellular, membrane-bound protein in BeWo cells that exhibited ceruloplasmin-like oxidase activity and reacted with a ceruloplasmin antibody.…”
Section: Basal Transport Of Ironmentioning
confidence: 99%